Nitrogen Source Preference and Growth Carbon Costs of Leucaena leucocephala (Lam.) de Wit Saplings in South African Grassland Soils - Nonkululeko Sithole; Zivanai Tsvuura; Kevin Kirkman; Anathi Magadlela (Plants, 2021)
Leucaena leucocephala (Fabaceae) is native to Central America and has invaded many climatic regions of the tropics. In South Africa, the species is categorized as an emerging or incipient weed used as fodder, timber, firewood and in erosion control on degraded habitats. The species is common along the eastern subtropical regions of KwaZulu-Natal (KZN) Province, where it invades grasslands, savannas and edges of forests. Soils of these ecosystems are characterized as nutrient deficient and acidic. Using a pot trial, we determined the effects of the nutrient addition treatments on microbial symbiosis, N nutrition and biomass accumulation of L. leucocephala under greenhouse conditions. After 180 days of growth, plants were harvested, and their utilization of N derived from the atmosphere and from the soil was quantified through determination of δ15N values. L. leucocephala maintained growth and N nutrition by relying on both atmospheric- and soil-derived N across all soil treatments. The NDFA was significantly higher in high P (N1 + P, N2 + P and N3 + P) soils. L. leucocephala was able to nodulate with intermediate and fast-growing strains from the Mesorhizobium and Rhizobium genus in N2 + P grown plants. This shows that L. leucocephala possesses traits that are successful in acquiring nutrients, especially in nutrient limited conditions, by establishing plant symbiosis with multiple bacteria and relying on extracting N from the soil and from the atmosphere through the symbiosis.